Sex, Love, and Letters : Writing Simone de Beauvoir - Coffin, Judith G., 1952- (Book collections on Project MUSE., 2020)
"An unexplored treasure trove of letters to Simone de Beauvoir from ordinary women and men around the world opens onto an unexpectedly intimate history of postwar France and the world, offering a riveting close-up of the kind of author-reader relationship that is so important to the history of ideas" --